Properties of nanocellulose and zirconia alumina on polymethylmethacrylate dental composite - Eva Febrina; Angela Evelyna; Andrie Harmaji; Bambang Sunendar (Dental Journal, 2023)
Background: Polymethylmethacrylate (PMMA) is one of the synthetic polymers generally used for temporary jacket crown restorations because of its good translucency, making its aesthetic value higher, but its mechanical properties, such as hardness and flexural strength are lower than composite resins. Hence, adding zirconia and cellulose filler is necessary to enhance its mechanical properties. Purpose: This is an experimental laboratory study to make nanocomposites with PMMA as a matrix with crystalline nanocellulose, zirconia, and alumina added as fillers. Methods: The crystalline nanocellulose filler was synthesized by acid hydrolysis. Zirconia and alumina were synthesized using the sol-gel technique and then characterized by transmission electron microscope and X-ray diffraction. The Micro Vickers hardness test and three-point bending tested mechanical properties. The analysis was carried out with a one-way analysis of variance, followed by a post hoc Tuckey’s test with a P < 0.05 taken as statistically significant. Results: The Micro Vickers hardness test showed the highest hardness in the group with a ratio of PMMA and zirconia-alumina filler of 50%: 2%: 48% (12.73 VHN). The results of the three-point bending test showed that the highest flexural strength was found in the control group (19.4 MPa). Conclusion: The addition of crystalline nanocellulose, zirconia, and alumina increase the hardness of the nanocomposite, while the flexural strength was lower than PMMA without filler addition.